PERCEIVED SELF-EFFICACY IN THE SOCIOCULTURAL SPHERE WITH MEXICAN UNIVERSITY STUDENTS. DIFFERENCES BETWEEN MEN AND WOMEN - Jesus Enrique Peinado; Jesus Viciana; Jose Rene Blanco; Humberto Blanco (European Scientific Journal, ESJ, 2014)
The aim of the present study was to compare the profiles of perceived self-efficacy in the sociocultural sphere between men and women university students. A total sample of 2,089 participants, 902 women and 1,187 men (average age = 18.23 ± .74 years) participated in this study. A quantitative approach with a descriptive and transversal survey design was applied. The results of the one-way multivariate analysis of variance, followed by the oneway univariate analyses of variance, showed that women reported statistically significant higher punctuations than men regarding the perceived self-efficacy in the promotion of culture and cultural identity (p < .001). Therefore, gender is an important variable when designing any kind of intervention for improving the perceived self-efficacy of students in a sociocultural sphere. Future research should apply these findings within other cultures.